Nursing management in the vaccine room: challenges and potentialities - Matheus Adriano Divino Pereira; Bruna Camargos de Lima; Deborah Amaral Donnini; Heloiza Maria Siqueira Renno; Valéria Conceição de Oliveira; Tarcísio Laerte Gontijo (Universidade Federal de Santa Maria, 2019)
Objective: to analyze nursing management in the vaccine room, with emphasis on supervision, in a medium-sized city of Minas Gerais, Brazil. Method: a descriptive, qualitative, unique case study. The data were organized and analyzed through theme/category-based content analysis. Results: the findings were organized into two analytical categories: "Intervening factors in the management of the vaccine room", addressing the challenges for supervision, the need for an instrument to standardize this activity, lack of work process organization and overloading of functions. The second category: "Potentialities for the management in the vaccine room" points out as potentiating factors the organization of the nurse's time and agenda and the need for an instrument that systematizes the supervision activities. Final Remarks: Most nurses understand the importance of supervision as a management tool, but do not perform it systematically.